Pelvic Inflammatory Disease During the Post-Partum Year - Barbara E. Mahon; M'hamed Temkit; Jane Wang; Marc B. Rosenman; Barry P. Katz (Hindawi Limited, 2005)
Objective. To investigate the occurrence of, and risk factors for, pelvic inflammatory disease (PID) occurring during the post-partum year.